2021
DOI: 10.1016/j.stemcr.2021.07.015
|View full text |Cite
|
Sign up to set email alerts
|

De novo DNA methyltransferases DNMT3A and DNMT3B are essential for XIST silencing for erosion of dosage compensation in pluripotent stem cells

Abstract: Summary Human pluripotent stem cells (hPSCs) have proven to be valuable tools for both drug discovery and the development of cell-based therapies. However, the long non-coding RNA XIST , which is essential for the establishment and maintenance of X chromosome inactivation, is repressed during culture, thereby causing erosion of dosage compensation in female hPSCs. Here, we report that the de novo DNA methyltransferases DNMT3A/3B are necessary for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 30 publications
(45 reference statements)
2
30
0
Order By: Relevance
“…XIST is expressed from one of two X chromosomes to archive X chromosome inactivation (XCI), and the expression is maintained in female somatic cells ( Augui et al., 2011 ; Penny et al., 1996 ). Previous studies have shown that XIST repression in female hPSCs causes the overexpression of X-linked genes and results in a poor differentiation ability ( Anguera et al., 2012 ; Fukuda et al., 2021 ; Mekhoubad et al., 2012 ; Patel et al., 2017 ). Therefore, XIST dysregulation may be one of the largest and most underestimated sources of variability hampering reproducibility and disease modeling in female hPSC research.…”
Section: Introductionmentioning
confidence: 99%
“…XIST is expressed from one of two X chromosomes to archive X chromosome inactivation (XCI), and the expression is maintained in female somatic cells ( Augui et al., 2011 ; Penny et al., 1996 ). Previous studies have shown that XIST repression in female hPSCs causes the overexpression of X-linked genes and results in a poor differentiation ability ( Anguera et al., 2012 ; Fukuda et al., 2021 ; Mekhoubad et al., 2012 ; Patel et al., 2017 ). Therefore, XIST dysregulation may be one of the largest and most underestimated sources of variability hampering reproducibility and disease modeling in female hPSC research.…”
Section: Introductionmentioning
confidence: 99%
“…X-inactivation is an experimentally tractable system to dissect epigenetic transcriptional regulation in PSCs. Much prior work has demonstrated that prolonged culture of female hPSCs results in loss of XIST RNA coating and erosion of X-inactivation 29 , 31 , 35 , 36 , 38 , 39 , 42 , 43 , 45 , 57 , 59 . Consistent with previous findings, our data rule out atmospheric O 2 concentration as a cause of XIST RNA loss in hESCs 35 , 43 , 45 , 68 – 70 .…”
Section: Discussionmentioning
confidence: 99%
“…The loss of XIST RNA expression in the hESCs is irreversible, in agreement with prior findings 35 , 38 , 39 . Of note, a recent report suggests that DNA methylation may contribute to the irreversibility of XIST RNA loss in cultured female hESCs that have undergone X-inactivation erosion 59 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human pluripotent stem cells, XIST expression is silenced by the de novo DNA methyltransferases DNMT3A and DNMT3B. 40
Figure 1 The long noncoding Xist RNA and its roles in X chromosome inactivation. (A) Genomic arrangement of XIST / Xist and its regulators in X inactivation center (XIC) in human and mouse.
…”
Section: Lncrna Xist and Mechanisms For X Chromoso...mentioning
confidence: 99%